2019
DOI: 10.1101/846725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutritional Programming Improves Dietary Plant Protein Utilization in Zebrafish Danio rerio

Abstract: 33Nutritional Programming (NP) has been shown to counteract the negative effects of dietary plant 34 protein (PP) by introducing PP at an early age towards enhancement of PP utilization during later 35 life stages. This study explored the effect of NP and its induction time on growth, expression of 36 appetite-stimulating hormones, and any morphological changes in the gut possibly responsible 37 for improved dietary PP utilization. At 3 days post-hatch (dph) zebrafish were distributed into 12 38 (3 L) tanks, 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Similarly, Zambonino‐Infante et al (2019) reported that European Bass Dicentrarchus labrax that were programmed with a high‐carbohydrate diet (34%) at mouth opening (6 dph) did not achieve higher weight gain compared to the non‐programmed fish. Conversely, Kwasek et al (2020) exposed Zebrafish to an SBM diet at 13 dph (stage of postmetamorphosis), and the programmed fish achieved a higher weight gain than non‐programmed individuals when an SBM diet was provided again to adults. This suggests that the NP method and fish age are critical for observing positive NP effects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, Zambonino‐Infante et al (2019) reported that European Bass Dicentrarchus labrax that were programmed with a high‐carbohydrate diet (34%) at mouth opening (6 dph) did not achieve higher weight gain compared to the non‐programmed fish. Conversely, Kwasek et al (2020) exposed Zebrafish to an SBM diet at 13 dph (stage of postmetamorphosis), and the programmed fish achieved a higher weight gain than non‐programmed individuals when an SBM diet was provided again to adults. This suggests that the NP method and fish age are critical for observing positive NP effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it appears that ingestion of the SBM diet alone does not suffice for NP to take effect. Perhaps if the NP stimulus was introduced at a later stage (in the form of a dry diet) when fish were fully metamorphosed (Kwasek et al 2020) or introduced in a different form (e.g., SBM‐enriched Artemia nauplii), an induced epigenetic change would have been reflected by the different phenotype of the NP‐PP group during the PP challenge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations